2012
DOI: 10.1002/stem.1021
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Fibroblast Growth Factor Protein Is a Determinant Factor in Regulating Self-Renewal, Differentiation, and Reprogramming in Human Pluripotent Stem Cells

Abstract: Fibroblast growth factor (FGF), transforming growth factor (TGF)/Nodal, and Insulin/insulin-like growth factor (IGF) signaling pathways are sufficient to maintain human embryonic stem cells (ESCs) and induced pluripotent stem cells in a proliferative, undifferentiated state. Here, we show that only a few FGF family members (FGF2, FGF4, FGF6, and FGF9) are able to sustain strong extracellular-signal-regulated kinase (ERK) phosphorylation and NANOG expression levels in human ESCs. Surprisingly, FGF1, which is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 36 publications
9
90
0
Order By: Relevance
“…FGF-MEK signaling is required for the maintenance of pluripotency through NANOG expression in hESCs [46], but not mESCs. Additionally, the FGF-MEK signaling pathway has been proposed to be required for mammalian neural induction [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…FGF-MEK signaling is required for the maintenance of pluripotency through NANOG expression in hESCs [46], but not mESCs. Additionally, the FGF-MEK signaling pathway has been proposed to be required for mammalian neural induction [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…signaling plays a role in SC self-renewal and differentiation (35)(36)(37)(38). We first employed RT-PCR analyses to characterize the expression of Fgfr genes in the CLs and in DESC spheres (Fig.…”
Section: Fgf Signaling In Descs Is Required For Sphere Formation and mentioning
confidence: 99%
“…A recent study demonstrated that among 17 FGFs tested, only FGF2, FGF4, FGF6, and FGF9 activate FGF receptor (FGFR) signaling in human embryonic stem cells (hESC). Moreover, normal FGFR activation was observed in hESC stimulated by stable FGF1 mutant but not its wild-type (wt) counterpart, suggesting that failure to signal in hESC may stem from instability in as many as 13 different members of FGF family [10].…”
Section: Introductionmentioning
confidence: 99%